A practical manual of diabetic foot care - Edmonds, M. E; Foster, Alethea V. M; Sanders, Lee J (Blackwell Publishing, 2008)
A practical clinical manual for the diagnosis, treatment - both medical and surgical - and the long-term care of foot problems in people with diabetes. The authors are world-renowned experts in this subject and they present the internationally recognised best practice. The clinical chapters are presented in a structured, colour-coded format to allow easy reference. The text also includes highlighted best clinical practice tips. Each chapter is accompanied by high-quality, full-colour photographs that provide excellent examples of the earliest presenting signs as well as illustrating the step-by-step guidance on treatment. This book is an essential manual for every healthcare professional involved in the care of patients with diabetes.
Keywords: Diabetic Foot; končetiny; Extremities; diabetická noha; podiatrie; diabetologie